Avaliação de sistema de climatização em Poedeiras comerciais - Kodaira, Vanessa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The animal welfare is one of the most discussed topics in the animal production chain and, with respect to poultry, many critics are aimed at the practices involved in the production of commercial eggs. Most of the large poultry companies producing eggs are opting for complete automation of their aviaries, but few of them offer the birds a suitable environment so that they can express their maximum productivity. The aim of this study was to compare the feasibility of an automated and acclimated and a non-acclimated aviary for laying hens in a poultry farm located in Bastos, SP. Dry bulb temperature, relative humidity and black globe temperature were recorded every 30 minutes, for one year, to determine the index of thermal comfort. Mortality of the birds, egg production and feed consumption were recorded daily. The variable of egg quality were recorded, analyzing 90 eggs from each shed, every 28 days. The calculations of feed costs, depreciation of equipment, labor and consumption of electrical power were used for the analysis of the profitability of the two sheds in study. At the same time, the surface temperature of the crests and feathered areas of the birds in various points of both sheds were analyzed, through infrared images, and hematological and biochemical parameters were analyzed and subsequently correlated with the index of thermal comfort, with the purpose of monitoring the heat stress of the birds, collecting blood from 15 laying hens of both sheds every 28 days. The results show that the acclimated system was effective, providing a reduction in the temperature and a thermal environment more suitable for creation of hens with higher hen-housed eggs and greater egg weight during the entire period of research and better egg shell quality in the summer period. When there are no failures in the supply of electrical energy, the acclimated system has better economic feasibility, providing ...

O bem-estar animal é um dos temas mais discutidos na cadeia produtiva animal e, no que diz respeito à avicultura, muitas críticas estão voltadas para as práticas envolvidas na produção de ovos comerciais. A maioria das grandes empresas avícolas produtoras de ovos caminha para a automação completa de aviários, mas poucas oferecem às aves um ambiente adequado para que elas possam expressar sua máxima produtividade. Objetivou-se comparar a viabilidade de um aviário automatizado e climatizado para poedeiras e de um não climatizado, em uma granja produtora de ovos localizada no município de Bastos-SP. Temperatura de bulbo seco, umidade relativa e temperatura de globo negro foram registradas durante um ano, a cada 30 minutos, para a determinação do índice de conforto térmico. Mortalidade das aves, produção de ovos e consumo de ração foram registrados diariamente. As variáveis da qualidade de ovos foram registradas, analisando-se 90 ovos de cada galpão, a cada 28 dias. Os cálculos de custos de ração, depreciação de equipamentos, mão-de-obra e consumo de energia elétrica foram utilizados para análise da lucratividade dos dois galpões em estudo. Paralelamente, analisou-se a temperatura superficial de cristas e áreas empenadas das aves em diversos pontos de ambos os galpões, através de imagens termográficas e parâmetros hematológicos e bioquímicos foram analisados e posteriormente correlacionados ao índice de conforto térmico, com o intuito de monitorar o estresse térmico das aves, coletando-se sangue de 15 aves de ambos os galpões a cada 28 dias. Os resultados mostram que o sistema climatizado foi eficaz, proporcionando a redução da temperatura e um ambiente térmico mais adequado à criação de aves com maior índice de ovos por ave alojada, maior peso de ovo durante todo o período da pesquisa e melhor qualidade externa dos ovos no período do verão. Quando não...
Keywords: Animais - Proteção; Energia eletrica - Consumo; Termografia; Análise econômico-financeira; Zootecnia; Animal welfare